2019
DOI: 10.1039/c9ce01031a
|View full text |Cite
|
Sign up to set email alerts
|

Designed synthesis of porous NiMoO4/C composite nanorods for asymmetric supercapacitors

Abstract: Porous and carbon composited binary transition metal oxide nanomaterials provide high ionic conductivity and electronic conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…To overcome the poor electronic conductivity of pristine NiMoO 4 , various NiMoO 4 /carbon composites have been synthesized by hybridizing NiMoO 4 nanostructures with graphene [ 30 , 31 ], carbon nanotubes [ 32 ], conducting polymers [ 33 ], and porous carbon architectures [ 34 , 35 ] Alternatively, intentional doping of NiMoO 4 with several kinds of heteroatoms such as Mn [ 36 , 37 ], P [ 38 ], Zn [ 39 ], Ce [ 40 ], or the creation of oxygen vacancies [ 14 , 41 , 42 , 43 ] in the lattice have recently been reported. In addition, NiMoO 4 has also been coupled with other metal oxides [ 44 , 45 , 46 , 47 , 48 , 49 ] or sulfides [ 50 , 51 , 52 ] to form heterostructure electrodes for supercapacitors with improved electrochemical performances.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the poor electronic conductivity of pristine NiMoO 4 , various NiMoO 4 /carbon composites have been synthesized by hybridizing NiMoO 4 nanostructures with graphene [ 30 , 31 ], carbon nanotubes [ 32 ], conducting polymers [ 33 ], and porous carbon architectures [ 34 , 35 ] Alternatively, intentional doping of NiMoO 4 with several kinds of heteroatoms such as Mn [ 36 , 37 ], P [ 38 ], Zn [ 39 ], Ce [ 40 ], or the creation of oxygen vacancies [ 14 , 41 , 42 , 43 ] in the lattice have recently been reported. In addition, NiMoO 4 has also been coupled with other metal oxides [ 44 , 45 , 46 , 47 , 48 , 49 ] or sulfides [ 50 , 51 , 52 ] to form heterostructure electrodes for supercapacitors with improved electrochemical performances.…”
Section: Introductionmentioning
confidence: 99%
“…Remanence magnetization, M r , is used to explain the magnetization strength of the synthesized compounds where the magnetization maintains when the external magnetic field is zero ( H = 0). [ 18 ] By magnifying the magnetization hysteresis curve (Figure 6b), it was found that the most saturation remanence ( M r ) is 0.20 for S 6 . The squareness ratio magnitude is obtained by the remanence and saturation magnetization ratio ( M rs = M r / M s ).…”
Section: Resultsmentioning
confidence: 99%
“…Application of NiMoO 4 as catalyst in a wide variety of industrial reactions, such as hydrodesulfurization, hydrodenitrogenation, water-gas shift reaction, steam reforming, etc., is suggested. [13] NiMoO 4 has been fabricated by different methods including hydrothermal, [14][15][16][17][18][19][20][21][22] thermal complex decomposition, [23,24] mechanochemical, [25] sonochemical, [26,27] microwave sintering, [28] sol-gel, [29,30] precipitation, [31,32] solvothermal, [33] microwave, [34] etc. However, solid-state route is one of the simplest and extensive synthesis methods to develop various types of materials for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the same method, when the precursor solution is non‐aqueous, the process is termed solvothermal, all other parameters being the same. Though relatively less frequent, there are many solvothermal instances in the open literature for the synthesis and tuning of NiMoO 4 224,226,259,274,281,289,292,326,350,382 . Figure 20 is to portray typical schematic hydrothermal/solvothermal schemes for synthesizing NiMoO 4 and relevant derivatives 54,382 .…”
Section: Preparation Methods Of Nimoo4 Materialsmentioning
confidence: 99%
“…This is so because this strategy offers the most convenient processes and yet conducive outcomes. Table 6 is to impart a brief account of a host of developments in catalytic properties of NiMoO 4 done involving heterostructures and hybrids 121,123,256‐382 . in many cases, doping, defect and/or morphology engineering have been amalgamated with the heterostructure for superior enhancement in catalytic properties either to generate more surface area or more population of active sites or for other special necessities as summarized in Table 6.…”
Section: Tuning the Properties Of Nimoo4 By Different Approachesmentioning
confidence: 99%